A new comonomer design for enhancing the pH-triggered LCST shift of thermosensitive polymers1. Issue 37 (7th October 2015) - Zhang, Hu; Marmin, Thomas; Cuierrier, Étienne; Soldera, Armand; Dory, Yves; Zhao, Yue
<x xml:space="preserve">Abstract</x> A rational comonomer design leads to a large pH-induced LCST shift.